Temperature Dependence of Optical Properties of MoS2 and WS2 Heterostructures Assessed by Spectroscopic Ellipsometry - Hoang Tung Nguyen; Van Long Le; Thi Mai Nguyen; Xuan Khuyen Bui; Thi Giang Nguyen; Nhat Linh Nguyen; Xuan Au Nguyen; Tae Jung Kim (Nanomaterials)
We report the complex dielectric function ε = ε1 + iε2 of MoS2/WS2 and WS2/MoS2 heterostructures and their constituent monolayers MoS2 and WS2 for an energy range from 1.5 to 6.0 eV and temperatures from 39 to 300 K. Comparisons between the optical properties of the heterostructures and their monolayers were conducted. Critical-point (CP) energies of the heterostructures were traced back to their origins in the monolayers. Low-temperature measurements confirmed the existence of only three excitonic CPs from 1.5 to 2.5 eV due to the overlap of trion B− of the MoS2 monolayer and exciton A0 of the WS2 monolayer. Due to the dielectric screening effect, most CPs exhibit red shifts in the heterostructures compared to their monolayer counterparts.